(untitled) (Italiano LinguaDue, 2024)
Il presente contributo riflette sul concetto di accessibilità glottodidattica con l’obiettivo di elaborare alcune proposte operative per facilitare e rendere significativo ed efficace l’apprendimento delle lingue straniere da parte di studenti con dislessia evolutiva. In primo luogo, si introducono le specificità cognitive ed affettive presenti nella classe di lingue; per poi approfondire le caratteristiche e i bisogni degli studenti con dislessia in quanto portatori di bisogni linguistici specifici. Si illustrano poi alcune strategie metodologiche per rendere accessibile l’insegnamento linguistico, con particolare attenzione all’adattabilità dei materiali didattici. Teaching languages to students with dyslexia: some pointers from spanish textbooks In this paper we reflect on the concept of language teaching accessibility with the aim of developing some operational proposals to facilitate and make the learning of foreign languages by students with dyslexia meaningful and effective. First, the cognitive and affective specificities in the language class are introduced; second, the characteristics and needs of students with dyslexia as well as their specific linguistic needs are presented in depth. We then illustrate some methodological strategies to make language teaching accessible, with particular attention to the adaptability of teaching materials.